2012
DOI: 10.1063/1.4707375
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ waves across gaps in non-excitable cells induced by femtosecond laser exposure

Abstract: Calcium is a second messenger in all cells for various cellular processes. It was found in astrocytes and neurons that femtosecond laser stimulation could induce Ca2+ wave propagation. In this work, a femtosecond laser with a power above a certain threshold was focused on single HeLa/HEK293T cells for Ca2+ mobilization. Several types of Ca2+ oscillation patterns were found in neighboring cells. The Ca2+ wave propagated very fast across 40-μm gaps in the Ca2+-free medium mediated by the adenosine-triphosphate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…These molecules then diffuse to neighbouring cells and activate purinergic receptors, including those coupled to GPCRs, resulting in a propagating intercellular Ca 2+ wave. They cite previous studies [3][4][5] ) and smaller spatial extent (~200 μm radius) as compared with μT-ICS waves (4.5 μm s −1 and ~400 μm radius, respectively) reported in our paper. Importantly, our studies employed human vascular endothelial cells (HUVECs) whose physiological function requires mechanosensitivity to hemodynamic shear stress.…”
mentioning
confidence: 86%
“…These molecules then diffuse to neighbouring cells and activate purinergic receptors, including those coupled to GPCRs, resulting in a propagating intercellular Ca 2+ wave. They cite previous studies [3][4][5] ) and smaller spatial extent (~200 μm radius) as compared with μT-ICS waves (4.5 μm s −1 and ~400 μm radius, respectively) reported in our paper. Importantly, our studies employed human vascular endothelial cells (HUVECs) whose physiological function requires mechanosensitivity to hemodynamic shear stress.…”
mentioning
confidence: 86%
“…A lot of cell processes are activated simultaneously and some of them can feedback to contribute to more Ca 2+ release, like ROS generated by two-photon excitation of endogenous absorbers [103] and/or oxidative stress to ER [104]. Interestingly, intercellular Ca 2+ wave propagation among excitable cells or non-excitable cells was also observed after the intracellular Ca 2+ release by femtosecond laser [6,98,105]. He et al proposed three possible mechanisms: 1) Ca 2+ signaling molecules such as ATP was released from the photostimulated cell and diffused away to excite Ca 2+ release in surrounding cells; 2) mechanical stress of shear flow by the plasma generation impacted surrounding cells to activate the release of Ca 2+ ; 3) mechanical stress of acoustic wave stimulated Ca 2+ release along its propagation [106].…”
Section: Biological Mechanism Studymentioning
confidence: 99%
“…He et al proposed three possible mechanisms: 1) Ca 2+ signaling molecules such as ATP was released from the photostimulated cell and diffused away to excite Ca 2+ release in surrounding cells; 2) mechanical stress of shear flow by the plasma generation impacted surrounding cells to activate the release of Ca 2+ ; 3) mechanical stress of acoustic wave stimulated Ca 2+ release along its propagation [106]. Several works suggested the Ca 2+ wave from a single cell stimulated by femtosecond laser at a relatively safe power was mediated by ATP which diffused in the cell medium and activated Ca 2+ release in surrounding cells through ATP receptors on cell membrane [91,105,107]. A recent work by Compton et al demonstrated the contribution of mechanical stress by a high-power nanosecond laser focused outside cell to Ca 2+ wave generation [108].…”
Section: Biological Mechanism Studymentioning
confidence: 99%
“…Previous studies of femtosecond stimulation of neurons [10][11][12][13][14][15][16][17][18][19][20] have proposed essentially two mechanisms induced by the laser: photo-disruption and photo-poration, where the transition from a dominant disruption mechanism to a dominant poration mechanism occurs at laser power densities ~ 5×10 11 W/cm 2 (e.g. ~35mW of 800nm, 100fs, 80MHz light focused with a 0.9 NA objective).…”
Section: Optical Stimulation Of Dissociated Cortical Neuronsmentioning
confidence: 99%
“…In neuroscience, NIR femtosecond lasers have been utilized as a noncontact, noninvasive alternative (or complement) to electrical stimulation of neurons and astrocytes [10][11][12]. Combined with fluorescence calcium imaging, this approach to neural stimulation has been applied to the study of neural activity, connectivity, and function [11,13,14].…”
Section: Optical Stimulation Of Dissociated Cortical Neuronsmentioning
confidence: 99%